2018
DOI: 10.1007/s10796-018-9864-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influential factors of continuance intention to use mobile Apps: Extending the expectation confirmation model

Abstract: The use of mobile applications (apps) has been growing in the world of technology, a phenomenon related to the increasing number of smartphone users. Even though the mobile apps market is huge, few studies have been made on what makes individuals continue to use a mobile app or stop using it. This study aims to uncover the factors that underlie the continuance intention to use mobile apps, addressing two theoretical models: Expectation confirmation model (ECM) and the extended unified theory of acceptance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
282
3
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(350 citation statements)
references
References 76 publications
44
282
3
21
Order By: Relevance
“…The empirical results showed that the satisfaction of previous learning experience, the confirmation of previous learning experience and perceived usefulness had significant effects on the willingness to continue using. Tam , Santos and Oliveira (2018) [19] based on the expectation-confirmation model (ECM) and extended unified theory of acceptance and use of technology (UTAUT2), discussed the factors of the willingness to continue using mobile applications, and found that the most important factors of the continuance intentions using mobile applications were satisfaction and confirmation expectation.…”
Section: B Expectation-confirmation Model In the Context Of E-readingmentioning
confidence: 99%
“…The empirical results showed that the satisfaction of previous learning experience, the confirmation of previous learning experience and perceived usefulness had significant effects on the willingness to continue using. Tam , Santos and Oliveira (2018) [19] based on the expectation-confirmation model (ECM) and extended unified theory of acceptance and use of technology (UTAUT2), discussed the factors of the willingness to continue using mobile applications, and found that the most important factors of the continuance intentions using mobile applications were satisfaction and confirmation expectation.…”
Section: B Expectation-confirmation Model In the Context Of E-readingmentioning
confidence: 99%
“…Perceived ease of use can induce users to engage more with the given technology [2,3], while complexity can have a negative impact on users' intention to adopt or reuse it [80]. For mobile apps usage, EE remains one of the crucial factors and significantly effects the behavioral intention of a user [81,82]. Similarly, operational comfort and complications involved can meaningfully influence users' intention to use mobile news apps.…”
Section: Effort Expectancy (Ee)mentioning
confidence: 99%
“…Habit was observed to have an effect on consumers' intention to use mobile payments [70], mobile apps [81], and the actual use of internet banking services [96]. Moreover, Barnes [97] stated that continuance intention can be determined by habit, while Tam and Santos [82] showed that for continuous intention to use mobile apps, habit is an influential predictor.…”
Section: Habit (Ha)mentioning
confidence: 99%
“…Positioning and timeliness refer to the value that LBA user perceive from having access to information and services in the right time and at the right place [73]. Users benefit expectation refers to their anticipated gained through using an information system [39,65]. When users expect more benefits from using LBAs, they are more likely to perceive the LBA useful.…”
Section: Hypotheses Developmentmentioning
confidence: 99%